Ionic liquids for the removal of pharmaceutical contaminants of emerging concern: a systematic review of extraction and purification strategies - Quijada-Maldonado, E (ELSEVIER, 2026)
Emerging pollutants, particularly pharmaceuticals and endocrine-disrupting compounds, are a growing global concern due to their persistence, toxicity, and limited removal in conventional wastewater treatment systems. Ionic liquids (ILs) have emerged as versatile solvents and functional media with the potential to overcome these limitations. This review aims to provide an overview of the state of the art regarding the use of ILs to purify, extract, or facilitate the elimination of pharmacological components from various media. Covering the period 2021-2025, this work systematically maps advances in IL applications, classifying them by structural families (imidazolium, pyridinium, pyrrolidinium, ammonium, cholinium, phosphonium, sulfonium, and others); by pharmaceutical groups (antibiotics, NSAIDs, hormones, CNS drugs, cardiovascular drugs, anticancer agents, and other bioactives); and by purification processes (extraction, absorption, permeation, separation, and other applications). Imidazolium-and ammonium-based ILs dominate current studies, while cholinium ILs stand out as greener, biocompatible alternatives, and functionalized ILs offer niche applications. Despite these advances, challenges remain regarding toxicity, cost, and scalability. Overall, ILs demonstrate strong potential for the sustainable management of pharmaceutical pollutants, with opportunities for task-specific design and alignment with green chemistry principles.